2002
DOI: 10.1038/sj.bjc.6600060
|View full text |Cite
|
Sign up to set email alerts
|

Schedule-dependent response of neuroblastoma cell lines to combinations of etoposide and cisplatin

Abstract: The growth inhibitory effects of cisplatin and etoposide on neuroblastoma cell lines were investigated in several scheduled combinations. Results were analyzed using median effect and combination index analyses. In all schedules in which cisplatin was administered prior to etoposide a synergistic effect was observed. Conversely, an antagonistic effect was seen in all schedules where etoposide was administered before cisplatin. The design of the widely used OPEC protocol (oncovins, platinum agents, epipodophyll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…At the highest dose tested on an HCT-8 cell line, MMC caused an increase in the S-phase cell fraction only, whereas ETO induced a cytostatic response with a cell block in the G2/ M phase, without significantly affecting the cells in the S-phase. These results are in agreement with the data of previous studies [37][38][39][40] : the ETO-induced block in G2/ M usually precedes the cellular death by apoptosis. G2/M is indeed a crucial phase for further cellular proliferation and an irreversible drug-induced G2/M arrest is associated with DNA double-strand breaks and extensive chromosome damage.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…At the highest dose tested on an HCT-8 cell line, MMC caused an increase in the S-phase cell fraction only, whereas ETO induced a cytostatic response with a cell block in the G2/ M phase, without significantly affecting the cells in the S-phase. These results are in agreement with the data of previous studies [37][38][39][40] : the ETO-induced block in G2/ M usually precedes the cellular death by apoptosis. G2/M is indeed a crucial phase for further cellular proliferation and an irreversible drug-induced G2/M arrest is associated with DNA double-strand breaks and extensive chromosome damage.…”
Section: Discussionsupporting
confidence: 83%
“…In chemotherapy trials, however, the main attention is usually paid to the problem of delivering a sufficient dose intensity. Nevertheless, many preclinical studies showed that changing the schedules of drugs resulted in a change from synergy to antagonism [40][41][42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…35 Likewise, the synergistic effect between topo poisons and cisplatin is well known. 36,37 In conclusion, our results suggest that DNA damage induced by topoisomerase II poisoning is a possible mechanism by which curcumin initiates apoptosis. The present results, when integrated with the broad literature available concerning curcumin as an anticancer safe compound, suggest that it should be borne in mind as a possible candidate not only for cancer prevention but also for cancer therapy.…”
Section: Discussionmentioning
confidence: 92%
“…7,8 Optimizing both ratio and sequence in a combined chemotherapy regimen is therefore essential to further lower the dosage relative to single-drug therapy needed to obtain a satisfactory therapeutic outcome. 7,9,10 This reduction of required therapeutic dosing (IC50 values) using drug combinations relative to single-drug chemotherapy has been recently demonstrated in vivo using various combination chemotherapy regimens and tumor models. 11−13 To implement synergistic delivery schemes, researchers have investigated the use of nanoparticles, 8,11,14 liposomes, 15,16 micelles, 17,18 polymer−drug conjugates (PDCs), 12,19 and hydrogels.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The complementary action of drugs targeting different metabolic pathways, in fact, provides enhanced therapeutic activity while requiring a significantly lower dosage. Recent work in this field has demonstrated that the therapeutic outcome depends not only on the molar ratio of the drugs in the cocktail but also on the schedule of administration, that is, the sequence at which the various drugs reach the target cells. , Optimizing both ratio and sequence in a combined chemotherapy regimen is therefore essential to further lower the dosage relative to single-drug therapy needed to obtain a satisfactory therapeutic outcome. ,, This reduction of required therapeutic dosing (IC50 values) using drug combinations relative to single-drug chemotherapy has been recently demonstrated in vivo using various combination chemotherapy regimens and tumor models. …”
Section: Introductionmentioning
confidence: 99%